Hubungan Konsumsi Sugar-Sweetened Beverages dan Aktivitas Fisik dengan Indeks Massa Tubuh pada Remaja Putri - Aisyiyah, Suci Agnanni; Pratamaningtyas, Susanti; Sendra, Eny; Wijayanti, Lumastari Ajeng (JURNAL ILKES : Jurnal Ilmu Kesehatan, 2024)
The prevalence of the problem of excess body mass index of adolescents with obesity category has increased worldwide over the past few decades including in Indonesia. Adolescent girls who consume sugar-sweetened beverages (SSB) with a frequency ≥ 1-6 times per week, and 81% do light physical activity. The purpose of the study was to determine the relationship between SSB consumption and physical activity with BMI in adolescent girls. Analytical research with a Cross-Sectional approach. Sampling was done by Proportionate Stratified Random Sampling, a sample of 90 adolescent girls at MAN 1 Kediri City. Data were collected using the BEVQ-15 and GPAQ questionnaires and analyzed with the Spearman Rank Test. Statistical tests showed p value = 0.000 < α (0.05) for the relationship between SSB consumption with BMI and p value = 0.005 < α (0.05) for the relationship between physical activity with BMI. SSB consumption and physical activity are associated with BMI. It is expected that young women maintain a normal body mass index by limiting the consumption of sugar-sweetened beverages, balancing the intake needs of nutrients in the body, and increasing physical activity.